Partitioning of sources of N2O from soil treated with different types of fertilizers by the acetylene inhibition method and stable isotope analysis. (10th May 2019) - Lin, Wei; Ding, Junjun; Li, Yuzhong; Zhang, Wei; Ahmad, Rasheed; Xu, Chunying; Mao, Lili; Qiang, Xiaojing; Zheng, Qian; Li, Qiaozhen
Abstract : Nitrous oxide (N2 O) is one of the major human‐induced greenhouse gases. It has a large potential for global warming, a long lifetime and can deplete ozone. In China, nitrogenous fertilizer is an important source of N2 O in agricultural soils, especially in vegetable production, where large amounts of nitrogen fertilizers are commonly used. Isotopomer ratios of N2 O, oxygen and bulk nitrogen isotope values ( δ 18 O and δ 15 N bulk ) and intramolecular 15 N site preferences (SP) have recently been used to identify the sources of N2 O. In this study, vegetable farm soil was incubated with manure (M), compound fertilizers (CF) and no fertilizers (NF). The acetylene inhibition method and a 15 N isotopic technique were used to reveal the most likely microbial processes leading to N2 O emissions. The results showed that the M treatment produced smaller N2 O emissions than the CF treatment of the soil. Nitrifier denitrification or denitrifier denitrification made the greatest contribution to N2 O production in the M treatment, accounting for approximately 60–89% of N2 O production, whereas it was 25–55% and 37–66% in the CF and NF treatments under non‐acetylene conditions, respectively. Under non‐acetylene conditions, N2 O reduction to N2 was largest for treatment M (32–90%), intermediate for NF (42–77%) and smallest for CF (20–51%). The results also showed that nitrifier nitrification and N2 O reduction were partly inhibited under acetylene conditions, with a relative contribution of 9–20% and 0–83% for M, 39–48% and 0–46% for CF, and 25–35% and 0–56% for NF, respectively. Our results suggest that analysing isotopomer ratios of N2 O with SP would be a practical approach for determining the contributions of microbial processes to N2 O emissions from different pools in soil. The results revealed that manure produced smaller N2 O emissions and promoted relatively larger rates of denitrification and N2 O reduction than compound fertilizers with the same amount of N, which indicated that complementing chemical with manure fertilizers might help to reduce N2 O emissions on vegetable‐producing land. Highlights: We investigated emissions and sources of N2 O with different types of fertilizers. For the same amount of N, manure produced less N2 O than compound fertilizer. Stable isotope analysis revealed that denitrification was the dominant process in the manure treatment. The acetylene inhibition method can supplement δ 15 N bulk compared with the SP model to assess N2 O reduction in soil.